Insidious. Chapter 2 [videorecording (DVD)] - Wan, James, 1977-; Wilson, Patrick, 1973-; Byrne, Rose; Hershey, Barbara, 1948-; Simpkins, Ty; Shaye, Lin, 1944- (Columbia, 2013)
The haunted Lambert family seeks to uncover the mysterious childhood secret that has left them dangerously connected to the spirit world.